Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1039/c5ra23425e
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in growth rate and productivity of spinach grown in hydroponics with iron oxide nanoparticles

Abstract: The uptake of iron oxide nanoparticles results in enhanced growth rate and productivity of spinach plant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(45 citation statements)
references
References 44 publications
2
40
1
2
Order By: Relevance
“…We used FTIR with ATR as a second noninvasive characterization technique requiring minimum sample preparation Journal of Nanomaterials to further understand the uptake and translocation of the NP fertilizer within the legumes [16,21]. The chemical composition of the shoot and leaves of the legumes grown from seeds presoaked in DI water, low-concentration NP fertilizer, and high-concentration NP fertilizer were investigated using an FTIR spectrometer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used FTIR with ATR as a second noninvasive characterization technique requiring minimum sample preparation Journal of Nanomaterials to further understand the uptake and translocation of the NP fertilizer within the legumes [16,21]. The chemical composition of the shoot and leaves of the legumes grown from seeds presoaked in DI water, low-concentration NP fertilizer, and high-concentration NP fertilizer were investigated using an FTIR spectrometer.…”
Section: Resultsmentioning
confidence: 99%
“…The results did not suggest any significant difference in the iron content among the three different dose conditions (control, low NP concentration, and high NP concentration) for each species of legumes. Previous studies involving iron NPs in the soil matrix after seed germination have reported a dosedependent relationship between the iron NP dosage and iron content within different parts of the plant [10,16,42]. However, when applied as only seed treatment, Srivastava et al found no significant difference in iron content in spinach plant leaves with a different iron pyrite (FeS 2 ) NP dosing [12,43].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fe 2 O 3 NPs can replace traditional Fe fertilizers in the cultivation of peanut plants[77] Vigna radiata FeNPs 2–6 nm+0.2% gum, +0.4% gum1 mM Fe 2+ ionsNatural biopolymer gum kondagogu as reducing and capping agent was usedThe radical length and biomass was increased in seeds exposed to Fe NPs in comparison to Fe 2+ ions. The α-amylase activity was increased in the seeds exposed to Fe NPs[78] Spinacea oleracea α-Fe 2 O 3 50 nm100, 150, 200 mg kg −1 of soilExperiments were performed in a solid hydroponic medium consisting of sawdust and coco peat and adequate amounts of waterPositive effects on spinach plant due to uptake of Fe 2 O 3 nanoparticles such as increase in stem and root lengths, biomass production and magnetic properties were observed[19] Lactuca sativa Core–shell NPs Fe/Fe 3 O 4 13/9 nm10, 20 mg L −1 15-days treatment of hydroponically grown lettuceThe nano-Fe/Fe 3 O 4 at 10 and 20 mg L −1 and FeSO 4 ·7H 2 O at 10 mg L −1 did not affect lettuce growth and chlorophyll content[71] Vigna unguiculata <100 nm25, 500 mg L −1 The elements were applied 56 and 72 days after sowing over the leaves, and data was collected after day 85Iron had significant effect on yield, leaf Fe content, stem Mg content, plasma membrane stability, and chlorophyll content, probably as a result of more efficient photosynthesis[79] Glycine max γ-Fe 2 O 3 (IONPS) and citrate coated IONPs 6 nm500, 1000 mg L −1 Plant physiological performance was assessed after foliar and soil IONPs fertilizationIONPs produced a significant positive effect on root elongation. IONPs-Cit significantly enhanced photosynthetic parameters when sprayed foliarly.…”
Section: Nanomaterials Based On Essential Metals and Their Use In Agrmentioning
confidence: 99%
“…In particular, it is known that metal oxide nanoparticles, such as copper oxide nanoparticles, exert negative effects on plants [2]. On the other hand, some NPs in suitable concentrations can enhance plant growth and could be used as nanofertilizers in agriculture to increase yields and thus decrease environmental pollution caused by classical fertilizers [3][4][5][6]. The biological effects of individual metals are more or less known, but even though combinations of xenobiotics are common in nature; their combined effects still need to be thoroughly investigated.…”
mentioning
confidence: 99%